Energy expenditure through physical activity in a population of community-dwelling Brazilian elderly: cross-sectional evidences from the Bambuí cohort study of aging - Juciany Rodrigues de Oliveira Ramalho; Maria Fernanda Lima-Costa; Josélia O. A. Firmo; Sérgio Viana Peixoto (Cadernos de Saúde Pública)
The aim of this study was to estimate physical activity energy expenditure among older adults. The study comprised 1,585 residents in Bambuí, Minas Gerais State, Brazil, aged > 60 years (91% of the town's total elderly), and examined the frequency and duration of 23 types of physical activity among them. Median energy expenditure was 975 MET.min/week (1,195.8 among men and 803.1 among women), declining significantly with age in both sexes. The prevalence of sedentary lifestyles (< 450 MET.min/week) was 31.2%. Unhurried walking accounted for about 1/3 of total energy expenditure. Multivariate analysis based on ordinal logistic regression showed inverse associations between energy expenditure and age and hospitalizations in both sexes. Among men, inverse associations were observed with smoking, number of chronic diseases and number of medical appointments. These results emphasize the need for effective strategies to increase physical activity in older elderly, and underscore the high prevalence of walking in this group.